A Systematic, Knowledge Space-Based Proposal on Quality by Design-Driven Polymeric Micelle Development - Bence Sipos; Gábor Katona; Ildikó Csóka (MDPI AG, 2021)
Nanoparticle research and development for pharmaceuticals is a challenging task in the era of personalized medicine. Specialized and increased patient expectations and requirements for proper therapy adherence, as well as sustainable environment safety and toxicology topics raise the necessity of well designed, advanced and smart drug delivery systems on the market. These stakeholder expectations and social responsibility of pharma sector open the space and call new methods on the floor for new strategic development tools, like Quality by Design (QbD) thinking. The extended model, namely the R&D QbD proved to be useful in case of complex and/or high risk/expectations containing or aiming developments. This is the case when we formulate polymeric micelles as promising nanotherapeutics; the risk assessment and knowledge-based quality targeted QbD approach provides a promising tool to support the development process. Based on risk assessment, many factors pose great risk in the manufacturing process and affect the quality, efficacy and safety profile. The quality-driven strategic development pathway, based on deep prior knowledge and an involving iterative risk estimation and management phases has proven to be an adequate tool, being able to handle their sensitive stability issues and make them efficient therapeutic aids in case of several diseases.